Analisis Komparatif Kinerja Keuangan pada Perusahaan PT. Telekomunikasi Indonesia TBK dan PT. Indosat TBK - Samsinar Samsinar; Diana Ambarwati; Nur Ali Agus Najibul Zamzam (FEB Universitas Maritim Semarang, 2023)
Healthy financial conditions are key to reducing risks and ensuring business continuity. Company management must carry out wise management in making decisions and preparing budget policies carefully. This research aims to determine the comparison of financial performance through profitability, liquidity and solvency of PT. Telekomunikasi Indonesia and PT. Indosat 2018-2021. This type of research is quantitative descriptive with a population of all PT financial reports. Telkom and PT. Indosat published by the Indonesian Stock Exchange. The research results show that PT. Telekomunikasi Indonesia shows a superior position when compared to PT. Indosat. The trend graph illustrates that PT. Telekomunikasi Indonesia Tbk has better performance compared to PT. Indosat. (1) PT Telekomunikasi Indonesia Tbk's Profitability Ratio is superior to PT Indosat in generating profits. (2) PT Telekomunikasi Indonesia's Liquidity Ratio is far superior to PT. Indosat. (3) Solvency Ratio of PT. Indonesian Telecommunication is superior compared to PT. Indosat. Based on the research results, PT Indosat and PT. Telecommunication needs to make better strategy or policy changes to manage its assets, assets and debts so that it can provide better profits in the future.